A composite cementing aid and a preparation method thereof
Patent Information
- Application Number
- CN202310271285.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-20
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2043-03-20
AI Technical Summary
[0004]然而,现有技术中,固井水泥助剂的抗盐和抗高温性能较差,当井底的温度或盐含量过高时,助剂中的分子链发生断裂、失活等问题,使得固井水泥的吸附能力大大减弱,严重会导致固井失败,出现安全事故
[0031](1)本发明中采用具有吸水性能的吸附剂和丙烯酰胺类单体为支撑材料,抗菌剂、硅烷单体和2-丙烯酰胺基-2-甲基丙磺酸能够与支撑材料内部交联分步聚合,使网状结构有规律的分布在聚合物链中,并且2-丙烯酰胺基-2-甲基丙磺酸的加入能够使得聚合物分子链中带有大量的磺酸根基团,从而使得复合固井助剂具备优异的抗温抗盐性能;
Smart Images

Figure BDA0004134749560000131 
Figure BDA0004134749560000132 
Figure BDA0004134749560000141
Abstract
Description
Technical Field
[0001] This invention relates to the field of oilfield chemicals technology, and in particular to a composite cementing aid and its preparation method. Background Technology
[0002] Cementing refers to the process of injecting cement into the annular space between the casing and the formation, allowing it to solidify and form a cement sheath. The cement sheath's bonding effect and hardness are used to seal off oil, gas, and water layers, prevent fluid cross-contamination, and protect the production layer. With the depletion of exploitable shallow oil and gas resources worldwide, oilfield exploration and development are increasingly moving towards deeper, ultra-deep wells and complex formations. This leads to increasingly stringent cementing quality requirements and the emergence of high-temperature, high-salinity environments at the wellbore, posing significant challenges to cementing. The ability of cement to maintain stable strength under long-term high-temperature, high-salinity conditions is a key factor in ensuring the long-term sealing integrity of the cement sheath in high-temperature oil wells and extending well life.
[0003] Cementing strength degrades rapidly under high-temperature environments, severely impacting the long-term integrity of deep wellbores and significantly shortening well life. Therefore, additives are typically added to cementing materials to improve its strength in high-temperature, high-salt environments.
[0004] However, existing cementing additives exhibit poor salt and high-temperature resistance. When the temperature or salt content at the bottom of the well is too high, the molecular chains in the additives break or become deactivated, significantly weakening the adsorption capacity of the cement and potentially leading to cementing failure and safety accidents. Therefore, it is necessary to research a composite cementing additive with better stability in high-temperature and high-salt environments. Summary of the Invention
[0005] This invention provides a composite cementing additive and its preparation method. The composite cementing additive has good stability in high temperature and high salinity environments. When combined with cementing cement, it can significantly improve the temperature and salt resistance of cementing cement and enhance the stability of the wellbore.
[0006] In a first aspect, the present invention provides a method for preparing a composite cementing additive, the method comprising the following steps:
[0007] (1) Add the adsorbent, antibacterial agent, acrylamide monomer, silane monomer and 2-acrylamido-2-methylpropanesulfonic acid to the solvent and mix well to obtain a mixed suspension;
[0008] (2) An initiator is added to the mixed suspension, and an intermediate polymer is obtained after polymerization.
[0009] (3) Add a curing agent to the intermediate polymer and obtain the composite cementing aid after curing reaction.
[0010] Preferably, in step (1), the adsorbent is at least one of bentonite or diatomaceous earth;
[0011] The antibacterial agent is at least one of 4-ethyl-4-daidzeinyl ethoxylate morpholine, 4-acryloyl morpholine, flumorpholine, zinc ricinoleate, zinc undecenoate, or zinc itaconic acid.
[0012] The acrylamide monomers include a first acrylamide monomer and a second acrylamide monomer;
[0013] The silane monomer is at least one of tetraallylsilane, propenyltriethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, dimethoxymethylvinylsilane, or methylvinyldiethoxysilane;
[0014] The solvent is at least one of dimethyl sulfoxide, dimethylformamide, dichloromethane, or tetrahydrofuran.
[0015] Preferably, in step (1), the particle size of the adsorbent is 1000-1200 mesh;
[0016] The first acrylamide monomer is acrylamide, and the second acrylamide monomer is at least one of 2-methylacrylamide, N,N-dimethylbisacrylamide, or N,N-methylenebisacrylamide.
[0017] More preferably, in step (1), the mass percentage of the first acrylamide monomer is 0.1-0.5%, and the mass percentage of the second acrylamide monomer is 99.5-99.9%.
[0018] Preferably, in step (2), before adding the initiator to the suspension, the step further includes adjusting the pH of the suspension to 8.0 to 14.0 using a pH adjuster;
[0019] The pH adjuster is a sodium hydroxide solution or a calcium hydroxide solution.
[0020] Preferably, in step (2), the initiator is at least one of benzoyl peroxide, dodecyl peroxide, azobisisobutyronitrile, sodium persulfate, potassium persulfate, or ammonium persulfate.
[0021] Preferably, in step (3), the curing agent is at least one of calcium carbonate, calcium gluconate, calcium lactate, calcium hydrogen phosphate, or diatomaceous earth.
[0022] Preferably, by mass parts, the amount of adsorbent added is 5-60 parts, the amount of antibacterial agent added is 0.15-0.5 parts, the amount of acrylamide monomer added is 15-89 parts, the amount of silane monomer added is 1.5-5 parts, the amount of 2-acrylamido-2-methylpropanesulfonic acid added is 5-15 parts, and the amount of solvent added is 53.3-502.5 parts;
[0023] The amount of initiator added is 0.1 to 0.3 parts, and the amount of curing agent added is 1 to 3 parts.
[0024] Preferably, in step (2), before the polymerization reaction, a step of introducing nitrogen gas into the reaction system is included, wherein the time for introducing nitrogen gas is 10 to 30 minutes.
[0025] More preferably, in step (2), the initiator is added to the mixed suspension in three stages, wherein the rate of initiator addition gradually decreases as the reaction time increases.
[0026] Preferably, in step (3), the curing reaction temperature is 25-30°C and the reaction time is 20-30 min;
[0027] After the curing reaction, the process also includes the steps of drying and pulverizing the composite cementing agent in sequence;
[0028] The drying temperature is 50–80°C, and the time is 20–50 hours.
[0029] Secondly, the present invention provides a composite cementing additive, which is prepared by any of the preparation methods described in the first aspect above.
[0030] Compared with the prior art, the present invention has at least the following beneficial effects:
[0031] (1) In this invention, an adsorbent with water absorption properties and acrylamide monomers are used as supporting materials. Antibacterial agents, silane monomers and 2-acrylamido-2-methylpropanesulfonic acid can crosslink and polymerize with the inside of the supporting material in a stepwise manner, so that the network structure is regularly distributed in the polymer chain. Furthermore, the addition of 2-acrylamido-2-methylpropanesulfonic acid can make the polymer molecular chain have a large number of sulfonate groups, thereby enabling the composite cementing aid to have excellent temperature and salt resistance properties.
[0032] (2) The composite cementing additive prepared in this invention is a hydrophilic network chain polymer with better water control performance. When it is mixed with cementing cement, it can increase the water content of cementing cement, reduce cementing casing adhesion, form a uniform film on the surface, and have a good anti-leakage effect. Furthermore, the composite additive is not easily decomposed at high temperature, which can effectively control the water loss of cement slurry, improve the solidification strength of cementing cement, and keep the strength of cement slurry stable for a long time at high temperature. Detailed Implementation
[0033] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are some embodiments of the present invention, but not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0034] This invention provides a method for preparing a composite cementing additive, the method comprising the following steps:
[0035] (1) Add the adsorbent, antibacterial agent, acrylamide monomer, silane monomer and 2-acrylamido-2-methylpropanesulfonic acid to the solvent and mix well to obtain a mixed suspension;
[0036] (2) An initiator is added to the mixed suspension, and an intermediate polymer is obtained after polymerization.
[0037] (3) Add a curing agent to the intermediate polymer and obtain the composite cementing aid after curing reaction.
[0038] This invention analyzes the moisturizing and crosslinking properties of cementing fluid under high temperature and high salinity conditions, as well as the mechanisms of cementing cement's delayed solidification, strength failure, and filtration loss under these conditions. Through extensive experimental research, adsorbents, antibacterial agents, acrylamide monomers, silane monomers, and 2-acrylamido-2-methylpropanesulfonic acid were selected as polymerizing monomers. During the polymerization process of each monomer, the water-absorbing adsorbents and acrylamide monomers serve as supporting materials. The antibacterial agents, silane monomers, and 2-acrylamido-2-methylpropanesulfonic acid can crosslink with the supporting materials and polymerize stepwise, resulting in a network structure that is regularly distributed in the polymer chain. Furthermore, because 2-acrylamido-2-methylpropanesulfonic acid contains sulfonic acid groups, the composite cementing additive possesses excellent temperature and salt resistance.
[0039] According to some preferred embodiments, in step (1), the adsorbent is at least one of bentonite or diatomaceous earth;
[0040] The antibacterial agent is at least one of 4-ethyl-4-daidzeinyl ethoxylate morpholine, 4-acryloyl morpholine, flumorpholine, zinc ricinoleate, zinc undecenoate, or zinc itaconic acid.
[0041] The acrylamide monomers include a first acrylamide monomer and a second acrylamide monomer;
[0042] The silane monomer is at least one of tetraallylsilane, propenyltriethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, dimethoxymethylvinylsilane, or methylvinyldiethoxysilane;
[0043] The solvent is at least one of dimethyl sulfoxide, dimethylformamide, dichloromethane, or tetrahydrofuran.
[0044] When preparing the mixed suspension, the adsorbent, antibacterial agent, acrylamide monomer, silane monomer and 2-acrylamido-2-methylpropanesulfonic acid can be added to the reaction vessel under stirring conditions. After stirring, each monomer dissolves to obtain the mixed suspension. This invention does not have any particular restrictions on the stirring speed and time, as long as it can ensure that each monomer dissolves.
[0045] This invention uses acrylamide monomers as the main chain, and adds adsorbents, antibacterial agents, silane monomers, and 2-acrylamido-2-methylpropanesulfonic acid as polymerizing monomers to prepare a composite cementing aid with a network structure. In this invention, the adsorbent is at least one of bentonite or diatomaceous earth. When the adsorbent includes both of the above components, the proportions between the components are not specifically limited. Meanwhile, the adsorbents in this invention are preferably pretreated bentonite and diatomaceous earth. High-temperature pretreatment of bentonite and diatomaceous earth not only improves their stability under high-temperature conditions, but also enhances their adsorption capacity. Introducing them into the composite additive improves its temperature and water retention properties. Furthermore, the rigid structure of the antibacterial agent and the sulfonate groups in 2-acrylamido-2-methylpropanesulfonic acid give the composite cementing additive excellent temperature and salt resistance. The silane monomer can form stable silicon-oxygen bonds with clay, which not only gives the product formed after the composite cementing additive is mixed with cementing cement good flowability, but also further improves the stability of the composite cementing additive in high-temperature and high-salt environments. The purity of 2-acrylamido-2-methylpropanesulfonic acid in this invention is preferably above 99.4%.
[0046] According to some preferred embodiments, in step (1), the particle size of the adsorbent is 1000 to 1200 mesh (for example, it can be 1000 mesh, 1100 mesh or 1200 mesh);
[0047] It should be noted that, in this invention, the bentonite and diatomaceous earth in the adsorbent are preferably prepared through a pretreatment process. This pretreatment process can adopt common processing techniques in the prior art. For example, the diatomaceous earth can be pretreated by the following process: diatomaceous earth is prepared by sequentially crushing, sorting, calcining, air classifying, microwave-enhanced acid leaching purification, and impurity removal. The bentonite in this invention is preferably a white or grayish-white clay with montmorillonite, albite, and quartz as the main components. The pretreatment process mainly involves acidification with inorganic acid, followed by water rinsing and drying. The above pretreatment can improve the particle size distribution and surface properties of diatomaceous earth, thereby improving the high-temperature water retention performance and dispersion performance of the composite cementing additive in cement slurry.
[0048] The first acrylamide monomer is acrylamide, and the second acrylamide monomer is at least one of 2-methylacrylamide, N,N-dimethylbisacrylamide, or N,N-methylenebisacrylamide.
[0049] According to some more preferred embodiments, in step (1), the mass percentage of the first acrylamide monomer in the acrylamide monomer is 0.1% to 0.5% (e.g., it can be 0.1%, 0.2%, 0.3%, 0.4%, or 0.5%), and the mass percentage of the second acrylamide monomer is 99.5% to 99.9% (e.g., it can be 99.5%, 99.6%, 99.7%, 99.8%, or 99.9%).
[0050] The acrylamide monomers in this invention are preferably composite acrylamide monomers composed mainly of acrylamide and doped with small amounts of 2-methylacrylamide, N,N-dimethylbisacrylamide or N,N-methylenebisacrylamide. Using this type of acrylamide monomer as the polymerization monomer is beneficial for further preparing composite cementing additives with excellent temperature and salt resistance, water retention and dispersibility.
[0051] According to some preferred embodiments, in step (2), before adding the initiator to the mixed suspension, the step further includes adjusting the pH value of the mixed suspension to 8.0 to 14.0 (e.g., 8.0, 9.0, 10.0, 11.0, 12.0, 13.0 or 14.0) using a pH adjuster;
[0052] The pH adjuster is a sodium hydroxide solution or a calcium hydroxide solution;
[0053] The initiator is at least one of benzoyl peroxide, dodecyl peroxide, azobisisobutyronitrile, sodium persulfate, potassium persulfate, or ammonium persulfate.
[0054] In this invention, a sodium hydroxide solution or calcium hydroxide solution with a mass concentration of 30-50% can be added dropwise to the mixed suspension. The pH adjuster can be added at a rate of 0.1-5.0 L / min. When the pH of the mixed suspension is adjusted to 8.0-14.0, the addition of the pH adjuster is stopped.
[0055] According to some preferred embodiments, in step (3), the curing agent is at least one of calcium carbonate, calcium gluconate, calcium lactate, calcium hydrogen phosphate, or diatomaceous earth.
[0056] According to some preferred embodiments, the amount of adsorbent added, by weight, is 5 to 60 parts (e.g., 5, 10, 20, 30, 40, 50, or 60 parts), the amount of antibacterial agent added is 0.15 to 0.5 parts (e.g., 0.15, 0.2, 0.3, 0.4, or 0.5 parts), and the amount of acrylamide monomer added is 15 to 89 parts (e.g., 15, 20, 30, 40, 50, 60, 70, or 80 parts). The amount of silane monomer added is 1.5 to 5 parts (e.g., 1.5, 2.0, 2.5, 3, 4 or 5 parts), the amount of 2-acrylamido-2-methylpropanesulfonic acid added is 5 to 15 parts (e.g., 5, 8, 10, 12 or 15 parts), and the amount of solvent added is 53.3 to 502.5 parts (e.g., 53.3, 80, 100, 200, 300, 400, 500 or 502.5 parts).
[0057] The amount of initiator added is 0.1 to 0.3 parts (e.g., 0.1, 0.2 or 0.3 parts), and the amount of curing agent added is 1 to 3 parts (e.g., 1, 2 or 3 parts).
[0058] In this invention, by comprehensively controlling the types and amounts of each polymerization monomer, the polymerization and curing reactions can be carried out smoothly, thereby successfully preparing a composite cementing additive with excellent temperature and salt resistance, good dispersion performance and excellent water control performance, which is beneficial to improving the stability and compressive strength of cementing cement in high temperature and high salt environment. For example, if the amount of adsorbent added is below the above range, the water absorption and retention performance of the composite cementing aid will be reduced. However, if the amount of adsorbent added is above the above range, the cross-linking performance of the adsorbent will be poor, which is not conducive to obtaining a stable network structure. In this invention, by controlling the amount of antibacterial agent added within the above range, not only can the high-temperature resistance of the composite cementing aid be improved, but it can also avoid the problem of reduced cementing wall strength caused by complex geological conditions and biological factors. If the amount of antibacterial agent added is below or above the above range, the high-temperature resistance and antibacterial performance of the composite cementing aid will decrease. At the same time, by controlling 2-acrylamido-2-methylpropanesulfonic acid within the above range in this invention, the composite cementing aid can contain a large number of sulfonate groups, thereby significantly improving the salt resistance of the composite cementing aid.
[0059] Furthermore, in this invention, the preferred amounts of each polymer monomer, by mass, are: 15-45 parts for the adsorbent (e.g., 15, 20, 25, 30, 40, or 45 parts), 0.3-0.5 parts for the antibacterial agent (e.g., 0.3, 0.4, or 0.5 parts), and 45-60 parts for the acrylamide monomer (e.g., 45, 48, 50, 55, 58, or 6...). The amount of silane monomer added is 3 to 5 parts (e.g., 3, 3.5, 4, 4.5 or 5 parts), the amount of 2-acrylamido-2-methylpropanesulfonic acid added is 10 to 15 parts (e.g., 10, 11, 12, 13, 14 or 15 parts), and the amount of solvent added is 98 to 251 parts (e.g., 98, 100, 120, 150, 180, 200, 220 or 251 parts).
[0060] The amount of initiator added is 0.1 to 0.3 parts (e.g., 0.1, 0.2 or 0.3 parts), and the amount of curing agent added is 2 to 3 parts (e.g., 2, 2.5 or 3 parts).
[0061] According to some preferred embodiments, in step (2), before the polymerization reaction, a step of introducing nitrogen gas into the reaction system is further included, wherein the time for introducing nitrogen gas is 15 to 30 min (for example, 15 min, 18 min, 20 min, 25 min or 30 min).
[0062] In this invention, because oxygen acts as a polymerization inhibitor and can affect the copolymerization reaction between the monomers, nitrogen gas is introduced to remove oxygen and ensure the polymerization reaction proceeds normally. Therefore, before adding the initiator to the mixed suspension to initiate the polymerization reaction, nitrogen is introduced into the reaction system to remove oxygen. In this invention, nitrogen gas can be introduced into the reaction system in stages until the nitrogen content in the system is not less than 99%, which is considered acceptable. Then, the initiator is added to the reaction system to initiate the polymerization reaction.
[0063] According to some preferred embodiments, in step (2), the temperature of the polymerization reaction is 40 to 80°C (for example, it can be 40°C, 50°C, 60°C, 70°C or 80°C), and the reaction time is 3 to 6 hours (for example, it can be 3 hours, 4 hours, 5 hours or 6 hours).
[0064] According to some preferred embodiments, in step (2), the viscosity of the intermediate polymer is 1 to 3 Pa·s (for example, it can be 1 Pa·s, 2 Pa·s or 3 Pa·s);
[0065] The initiator is added to the mixed suspension in stages, with the initiator being added at a rate of 0.1 to 2 mL / min in each stage (e.g., 0.1 mL / min, 0.5 mL / min, 0.8 mL / min, 1 mL / min, 1.5 mL / min, 1.8 mL / min or 2 mL / min).
[0066] According to some preferred embodiments, in step (2), an initiator is added to the mixed suspension in three stages, wherein the rate of initiator addition gradually decreases as the reaction time increases.
[0067] In this invention, when adding the initiator to the mixed suspension, it is preferable to add the initiator to the mixed suspension in stages to initiate the polymerization reaction. Furthermore, in combination with the characteristics of the polymerization reaction, the addition rate of the initiator is gradually reduced as the polymerization reaction time increases. This not only ensures sufficient reaction between the various monomers, but also reduces the generation of byproducts during the reaction.
[0068] It should be noted that in this invention, a segmented variable speed pump can be used to add the initiator to the mixed suspension. When pumping the initiator, it can be added in three stages according to the polymerization reaction time. For example, when the polymerization reaction time is 3 hours, the initiator can be pumped at a constant rate of 0.8 mL / min in the first stage (first hour), at a constant rate of 0.6 mL / min in the second stage (second hour), and at a constant rate of 0.4 mL / min in the third stage (third hour). When the viscosity of the intermediate polymer reaches the required level, the addition of the initiator can be stopped.
[0069] According to some preferred embodiments, in step (2), the temperature of the curing reaction is 25-30°C (for example, it can be 25°C, 26°C, 27°C, 28°C, 29°C or 30°C), and the reaction time is 20-30 min (for example, it can be 20 min, 22 min, 25 min, 28 min or 30 min);
[0070] After the curing reaction, the process also includes the steps of drying and pulverizing the composite cementing agent in sequence;
[0071] The drying temperature is 50–80°C (e.g., 50°C, 60°C, 65°C, 70°C, 75°C, or 80°C), and the time is 20–50 hours (e.g., 20 hours, 30 hours, 40 hours, or 50 hours).
[0072] In this invention, an intermediate polymer is cured with a curing agent containing calcium salts or diatomaceous earth, and then pulverized after high-temperature drying to prepare a composite cementing additive with solid particles. This composite cementing additive exhibits good dispersibility and ease of use in cement slurry. Furthermore, in this invention, the intermediate polymer and curing agent are cured at room temperature (25–30°C) by high-speed stirring at a speed of 700–1500 r / min.
[0073] The present invention also provides a composite cementing aid, which is prepared by the preparation method provided in the present invention.
[0074] To more clearly illustrate the technical solution and advantages of the present invention, the following describes in detail a composite cementing additive and its preparation method through several embodiments.
[0075] In the following examples, the mass of solvent, adsorbent, antibacterial agent, acrylamide monomer, silane monomer, 2-acrylamido-2-methylpropanesulfonic acid, initiator and curing agent are expressed in parts by weight.
[0076] Example 1:
[0077] (1) Under stirring conditions, 195 parts of solvent (dimethyl sulfoxide) were added to the reaction vessel, followed by 59.5 parts of adsorbent (30 parts of diatomaceous earth and 29.5 parts of bentonite, both with a particle size of 1100 mesh), 0.5 parts of antibacterial agent (4-ethyl-4-daidzein ethoxylate morpholine), 28.5 parts of acrylamide monomer (of which acrylamide accounts for 99.5% of acrylamide monomer, and 2-methylacrylamide and N,N-dimethylbisacrylamide account for 0.5% of acrylamide monomer), 3 parts of silane monomer (tetraallylsilane) and 6 parts of 2-acrylamido-2-methylpropanesulfonic acid. The mixture was stirred and mixed to obtain a mixed suspension.
[0078] (2) Add pH adjuster (40% sodium hydroxide solution) dropwise to the mixed suspension at a rate of 2 L / min until the pH value of the mixed suspension reaches 9.0; after purging nitrogen into the mixed suspension for 10 min, raise the temperature of the reaction system to 45℃, and then add the initiator in three stages using a segmented variable speed pump. In the first stage of polymerization (first 2 h), the initiator is pumped at a uniform rate of 0.8 mL / min; in the second stage (3-4 h), the initiator is pumped at a uniform rate of 0.6 mL / min; and in the third stage (5 h), the initiator is pumped at a uniform rate of 0.4 mL / min. The polymerization reaction time is 5 h. After the polymerization reaction, an intermediate polymer is obtained with a viscosity of 0.8 Pa·s.
[0079] (3) Add 2.5 parts of curing agent (calcium carbonate) to the intermediate polymer and stir at a speed of 800 r / min for 30 min at room temperature (25℃) to carry out the curing reaction. The viscosity of the cured product is 0.85 Pa.s. Then place it in a steam rotary furnace at 60℃ to dry for 30 h and then crush it to obtain the composite cementing aid.
[0080] Example 2:
[0081] (1) Under stirring conditions, 190 parts of solvent (dimethylformamide) were added to the reaction vessel, followed by 49.5 parts of adsorbent (25 parts of diatomaceous earth and 24.5 parts of bentonite, all with a particle size of 1000 mesh), 0.5 parts of antibacterial agent (4-acryloylmorpholine), 28.5 parts of acrylamide monomer (of which acrylamide accounts for 99.5% of acrylamide monomer, and 2-methylacrylamide and N,N-dimethylbisacrylamide account for 0.5% of acrylamide monomer), 4 parts of silane monomer (vinyltrimethoxysilane) and 10 parts of 2-acrylamido-2-methylpropanesulfonic acid were stirred and mixed to obtain a mixed suspension;
[0082] (2) Add pH adjuster (40% sodium hydroxide solution) dropwise to the mixed suspension at a rate of 2 L / min until the pH value of the mixed suspension reaches 10.0; after purging nitrogen into the mixed suspension for 15 min, raise the temperature of the reaction system to 60℃, and then add the initiator in three stages using a segmented variable speed pump. In the first stage of polymerization, the initiator is pumped at a uniform rate of 0.8 mL / min; in the second stage, the initiator is pumped at a uniform rate of 0.6 mL / min; and in the third stage, the initiator is pumped at a uniform rate of 0.4 mL / min. The polymerization reaction time is 6 h. After the polymerization reaction, an intermediate polymer is obtained with a viscosity of 0.8 Pa·s.
[0083] (3) Add 2.5 parts of curing agent (diatomaceous earth) to the intermediate polymer and stir at a speed of 1000 r / min for 30 min at room temperature (25℃) to carry out the curing reaction. The viscosity of the cured product is 0.85 Pa.s. Then place it in a steam rotary furnace at 70℃ to dry for 30 h and then crush it to obtain the composite cementing aid.
[0084] Example 3:
[0085] (1) Under stirring conditions, 195 parts of solvent (dimethylformamide) were added to the reaction vessel, followed by 39.5 parts of adsorbent (20 parts of diatomaceous earth and 19.5 parts of bentonite, both with a particle size of 1200 mesh), 0.5 parts of antibacterial agent (4-ethyl-4-daidzein methyl morpholine), 37.5 parts of acrylamide monomer (of which acrylamide accounts for 99.5% of acrylamide monomer, and 2-methylacrylamide and N,N-dimethylbisacrylamide account for 0.5% of acrylamide monomer), 5 parts of silane monomer (tetraallylsilane) and 15 parts of 2-acrylamido-2-methylpropanesulfonic acid. The mixture was stirred and mixed to obtain a mixed suspension.
[0086] (2) Add pH adjuster (40% sodium hydroxide solution) dropwise to the mixed suspension at a rate of 2 L / min until the pH value of the mixed suspension reaches 9.0; after purging nitrogen into the mixed suspension for 10 min, raise the temperature of the reaction system to 45℃, and then add the initiator in three stages using a segmented variable speed pump. In the first stage of polymerization, the initiator is pumped at a uniform rate of 0.8 mL / min; in the second stage, the initiator is pumped at a uniform rate of 0.6 mL / min; and in the third stage, the initiator is pumped at a uniform rate of 0.4 mL / min. The polymerization reaction time is 5 h. After the polymerization reaction, an intermediate polymer is obtained with a viscosity of 0.8 Pa·s.
[0087] (3) Add 2.5 parts of curing agent (calcium carbonate) to the intermediate polymer and stir at a speed of 800 r / min for 30 min at room temperature (25℃) to carry out the curing reaction. The viscosity of the cured product is 0.85 Pa.s. Then place it in a steam rotary furnace at 60℃ to dry for 30 h and then crush it to obtain the composite cementing aid.
[0088] Example 4:
[0089] Example 4 is basically the same as Example 1, except that in step (1), 190 parts of solvent (dimethylformamide) are added to the solvent in the reaction vessel, followed by 29.5 parts of adsorbent (15 parts of diatomaceous earth and 14.5 parts of bentonite, both with a particle size of 1100 mesh), 0.5 parts of antibacterial agent (4-ethyl-4-daidzein methyl morpholine), 47.5 parts of acrylamide monomer (of which acrylamide accounts for 99.5% of acrylamide monomer, and 2-methylacrylamide and N,N-dimethylbisacrylamide account for 0.5% of acrylamide monomer), 5 parts of silane monomer (tetraallylsilane) and 15 parts of 2-acrylamido-2-methylpropanesulfonic acid are stirred and mixed to obtain a mixed suspension.
[0090] Example 5:
[0091] Example 5 is basically the same as Example 1, except that in step (1), 190 parts of solvent (dimethylformamide) are added to the solvent in the reaction vessel, followed by 29.5 parts of adsorbent (15 parts of diatomaceous earth and 14.5 parts of bentonite, both with a particle size of 1100 mesh), 0.5 parts of antibacterial agent (4-ethyl-4-daidzeinyl morpholine), 47.5 parts of acrylamide monomer (of which acrylamide accounts for 99.5% of acrylamide monomer, and 2-methylacrylamide and N,N-dimethylbisacrylamide account for 0.5% of acrylamide monomer), 5 parts of silane monomer (tetraallylsilane) and 15 parts of 2-acrylamido-2-methylpropanesulfonic acid are stirred and mixed to obtain a mixed suspension.
[0092] Example 6:
[0093] Example 6 is basically the same as Example 1, except that in step (1), 190 parts of solvent (dimethylformamide) are added to the solvent in the reaction vessel, followed by 19.5 parts of adsorbent (10 parts of diatomaceous earth and 9.5 parts of bentonite, both with a particle size of 1100 mesh), 0.5 parts of antibacterial agent (4-ethyl-4-daidzeinyl morpholine), 57.5 parts of acrylamide monomer (of which acrylamide accounts for 99.5% of acrylamide monomer, and 2-methylacrylamide and N,N-dimethylbisacrylamide account for 0.5% of acrylamide monomer), 5 parts of silane monomer (tetraallylsilane) and 15 parts of 2-acrylamido-2-methylpropanesulfonic acid are stirred and mixed to obtain a mixed suspension.
[0094] Example 7:
[0095] Example 7 is basically the same as Example 6, except that in step (1), the adsorbent is 4 parts.
[0096] Example 8:
[0097] Example 8 is basically the same as Example 6, except that in step (1), the amount of antibacterial agent is 0.6 parts.
[0098] Example 9:
[0099] Example 9 is basically the same as Example 6, except that in step (1), the silane monomer is 4 parts.
[0100] Example 10:
[0101] Example 10 is basically the same as Example 6, except that in step (1), 2-acrylamido-2-methylpropanesulfonic acid is 4 parts.
[0102] Example 11:
[0103] Example 11 is basically the same as Example 6, except that in step (2), the initiator is added to the mixed suspension at a rate of 0.8 mL / min all at once, and the intermediate polymer is obtained after 4 hours of polymerization.
[0104] Comparative Example 1:
[0105] Comparative Example 1 is basically the same as Example 1, except that in step (1), the mixed suspension does not contain an adsorbent.
[0106] Comparative Example 2:
[0107] Comparative Example 2 is basically the same as Example 1, except that in step (1), the mixed suspension does not contain an antibacterial agent.
[0108] Comparative Example 3:
[0109] Comparative Example 3 is basically the same as Example 1, except that in step (1), the mixed suspension does not contain silane monomers.
[0110] Ten parts of each of the composite cementing additives obtained in Examples 1 to 11 and Comparative Examples 1 to 3 were dissolved in 48 parts of water. The aqueous solution was placed in a stirrer and stirred at a speed of 3500±300 r / min. 100 parts of a mixture of cementing cement and 35 parts of dry quartz sand powder were weighed and added to the stirrer within 20 seconds. The mixture was then stirred at a speed of 12000±500 r / min for 40 seconds to obtain a cementing slurry system. 30% sodium chloride and potassium chloride were added to the cementing slurry, and the mixture was stirred at a speed of 3500±300 r / min to obtain a salt-containing cementing slurry system.
[0111] The obtained cementing slurry and salt-containing cementing slurry system were subjected to performance tests. In this test example, the comprehensive performance of the composite cementing additives provided in the examples and comparative examples was evaluated according to the petroleum and natural gas industry standard SY / T5504.2-2013 "Evaluation Method of Oil Well Cement Additives" and the national standard GB / T19139-2012 "Test Method of Oil Well Cement". The test results are shown in Table 1 and Table 2.
[0112] Table 1
[0113]
[0114] Note: API dehydration test conditions: 90℃ * 7.1MPa * 30min; thickening test conditions: 120℃ * 80MPa * 60min
[0115] Table 2
[0116]
[0117]
[0118] As shown in Table 1, the cement slurry obtained by mixing the composite cementing additive prepared in the embodiments of the present invention with cementing cement exhibits good stability, good fluidity, low water loss, and a thickening time of approximately 4–5 hours. The cement injection pressure is reduced, meeting the requirements for safe cementing in the field. As shown in Table 2, although the compressive strength of the cement slurry with the added composite cementing additive slightly decreases after curing at high temperatures of 120–180℃ for 3 days and 7 days, it still maintains good overall stability.
[0119] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a composite cementing additive, characterized in that, The preparation method includes the following steps: (1) The adsorbent, antibacterial agent, acrylamide monomer, silane monomer and 2-acrylamido-2-methylpropanesulfonic acid are added to a solvent and mixed to obtain a mixed suspension; the antibacterial agent is at least one of 4-ethyl-4-daidzeinyl morpholine, 4-acryloylmorpholine, flumorpholine, zinc ricinoleate, zinc undecanoate or zinc itaconic acid; the adsorbent is at least one of bentonite or diatomaceous earth; The acrylamide monomers include a first acrylamide monomer and a second acrylamide monomer; the first acrylamide monomer is acrylamide, and the second acrylamide monomer is at least one selected from 2-methylacrylamide, N,N-dimethylbisacrylamide, or N,N-methylenebisacrylamide; in the acrylamide monomers, the mass percentage of the first acrylamide monomer is 0.1~0.5%, and the mass percentage of the second acrylamide monomer is 99.5~99.9%. (2) An initiator is added to the mixed suspension, and an intermediate polymer is obtained after polymerization. (3) Add a curing agent to the intermediate polymer and obtain the composite cementing aid after curing reaction; the curing agent is at least one of calcium carbonate, calcium gluconate, calcium lactate, calcium hydrogen phosphate or diatomaceous earth; By mass, the amount of adsorbent added is 5-60 parts, the amount of antibacterial agent added is 0.15-0.5 parts, the amount of acrylamide monomer added is 15-89 parts, the amount of silane monomer added is 1.5-5 parts, the amount of 2-acrylamido-2-methylpropanesulfonic acid added is 5-15 parts, the amount of solvent added is 53.3-502.5 parts; the amount of initiator added is 0.1-0.3 parts, and the amount of curing agent added is 1-3 parts.
2. The preparation method according to claim 1, characterized in that, In step (1): The adsorbent is at least one of bentonite or diatomite. The acrylamide monomers include a first acrylamide monomer and a second acrylamide monomer; The silane monomer is at least one of tetraallylsilane, propenyltriethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, dimethoxymethylvinylsilane, or methylvinyldiethoxysilane; The solvent is at least one of dimethyl sulfoxide, dimethylformamide, dichloromethane, or tetrahydrofuran.
3. The preparation method according to claim 2, characterized in that, In step (1): The particle size of the adsorbent is 1000~1200 mesh.
4. The preparation method according to claim 1, characterized in that, In step (2), before adding the initiator to the mixed suspension, the pH value of the mixed suspension is adjusted to 8.0~14.0 using a pH adjuster; The pH adjuster is a sodium hydroxide solution or a calcium hydroxide solution; and / or The initiator is at least one of benzoyl peroxide, dodecyl peroxide, azobisisobutyronitrile, sodium persulfate, potassium persulfate, or ammonium persulfate.
5. The preparation method according to claim 1, characterized in that, In step (2): Before the polymerization reaction, the process also includes a step of introducing nitrogen gas into the reaction system for 10-30 minutes; and / or The polymerization reaction is carried out at a temperature of 40-80°C for 3-6 hours.
6. The preparation method according to claim 1, characterized in that, In step (2): The viscosity of the intermediate polymer is 1~3 Pa·s; The initiator is added to the mixed suspension in stages, with the initiator being added at a rate of 0.1 to 2 mL / min in each stage; the initiator is added to the mixed suspension in three stages, wherein the rate of initiator addition gradually decreases as the reaction time increases.
7. The preparation method according to claim 1, characterized in that, In step (3): The curing reaction is carried out at a temperature of 25-30°C for 20-30 minutes. After the curing reaction, the process also includes the steps of drying and pulverizing the composite cementing agent in sequence; The drying temperature is 50~80℃, and the time is 20~50h.
8. A composite cementing additive, characterized in that, It is prepared by any one of the preparation methods according to claims 1 to 7.
Citation Information
Patent Citations
High-polymer curing resin of coating agent for drilling fluid
CN110358511A
High-temperature-resistant salt-resistant organic silicon filtrate reducer as well as preparation method and application thereof
CN114989348A